Constructing a novel mitochondrial metabolism-related genes signature to evaluate tumor immune microenvironment and predict survival of colorectal cancer - Wang, Hou; Zhang, Kai; Ning, Guang (Frontiers in Medicine, 2025)
BackgroundColorectal cancer (CRC) is a highly lethal gastrointestinal malignancy with substantial global health implications. Although mitochondrial metabolism genes play a crucial role in CRC development, their prognostic significance remains unclear.MethodsThis study systematically analyzed the expression and prognostic value of mitochondrial metabolism-related genes in CRC patients, establishing a risk model using data from TCGA and GEO databases. We also investigated the tumor microenvironment (TME), immune cell infiltration, tumor mutation burden, microsatellite instability (MSI), and drug sensitivity. Core mitochondrial metabolism-related gene, TMEM86B was identified and its functions validated through cell-based assays and in vivo mouse models.ResultsFifteen mitochondrial metabolism-related genes were identified, including HSD3B7, ORC1, GPSM2, NDUFA4L2, CHDH, LARS2, TMEM86B, FABP4, TNFAIP8L3, HMGCL, GDE1, ACOX1, ARV1, HDC, and GSR. The nomogram, which incorporates independent prognostic genes TMEM86B, TNFAIP8L3, HDC, and key clinical features pTNM stage (pathological Tumor-Node-Metastasis), age, was created to predict patient outcomes. Notable differences in immune cell infiltration were observed between risk groups. The risk score was associated with TME genes and immune checkpoints, indicating an immunosuppressive environment in high-risk groups. Furthermore, TIDE analysis revealed that integrating the risk score with immune score, stromal score, or microsatellite status improved the prediction of immunotherapy response across different CRC patient subgroups. Core mitochondrial metabolism-related gene, TMEM86B promotes colorectal cancer progression by enhancing cell proliferation, migration, and invasion, and its downregulation significantly inhibits tumor growth both in vitro and in vivo.ConclusionOur findings indicate that the risk model associated with mitochondrial metabolism may serve as a dependable prognostic indicator, facilitating tailored therapeutic strategies for CRC patients. TMEM86B promotes colorectal cancer progression, and its downregulation inhibits tumor growth in vitro and in vivo.